2010
DOI: 10.1103/physrevlett.105.136805
|View full text |Cite
|
Sign up to set email alerts
|

Atomically ThinMoS2: A New Direct-Gap Semiconductor

Abstract: The electronic properties of ultrathin crystals of molybdenum disulfide consisting of N = 1, 2, ... 6 S-Mo-S monolayers have been investigated by optical spectroscopy. Through characterization by absorption, photoluminescence, and photoconductivity spectroscopy, we trace the effect of quantum confinement on the material's electronic structure. With decreasing thickness, the indirect band gap, which lies below the direct gap in the bulk material, shifts upwards in energy by more than 0.6 eV. This leads to a cro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

435
9,406
30
43

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13,873 publications
(9,914 citation statements)
references
References 38 publications
435
9,406
30
43
Order By: Relevance
“…Among various 2D materials, MoS 2 has shown excellent properties in optoelectronic applications due to its suitable band gap value,5, 6 relatively high carrier mobility,2, 7 high light absorbance,3, 8 and, more importantly, good stability,9, 10 and brilliant optoelectronic properties 1, 7, 11, 12. However, pure MoS 2 ‐based optoelectronic devices are usually limited to infrared light detection and lower photoelectric conversion efficiency (PCE) because of the direct band gap of 1.8 eV for single‐layered MoS 2 sheet5, 6 and the picosecond ultrashort carrier lifetime 13, 14.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among various 2D materials, MoS 2 has shown excellent properties in optoelectronic applications due to its suitable band gap value,5, 6 relatively high carrier mobility,2, 7 high light absorbance,3, 8 and, more importantly, good stability,9, 10 and brilliant optoelectronic properties 1, 7, 11, 12. However, pure MoS 2 ‐based optoelectronic devices are usually limited to infrared light detection and lower photoelectric conversion efficiency (PCE) because of the direct band gap of 1.8 eV for single‐layered MoS 2 sheet5, 6 and the picosecond ultrashort carrier lifetime 13, 14.…”
Section: Introductionmentioning
confidence: 99%
“…Among various 2D materials, MoS 2 has shown excellent properties in optoelectronic applications due to its suitable band gap value,5, 6 relatively high carrier mobility,2, 7 high light absorbance,3, 8 and, more importantly, good stability,9, 10 and brilliant optoelectronic properties 1, 7, 11, 12. However, pure MoS 2 ‐based optoelectronic devices are usually limited to infrared light detection and lower photoelectric conversion efficiency (PCE) because of the direct band gap of 1.8 eV for single‐layered MoS 2 sheet5, 6 and the picosecond ultrashort carrier lifetime 13, 14. To conquer the drawbacks of wavelength and lifetime limitations, van der Waals heterostructures,15 or lateral heterostructures,16, 17 which are made by stacking a monolayer on the top of another monolayer or a few‐layer crystal or controlled by epitaxial growth of lateral heterojunction, are developed and show great potential for designing high‐performance 2D material‐based photodetectors owing to the combined advantages and synergetic effects of different 2D materials with various band gaps and work functions,18, 19, 20 and the ultrafast layer‐to‐layer transfer speed of carriers 21.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike gapless graphene, these 2DLMCs have bandgaps in comparison to commercially silicon semiconductors, and the bandgaps can be further adjusted in a large range with thickness change. For example, it has been reported that MoS 2 has emerged with a direct bandgap of 1.8 eV when reduced the thickness to monolayer 25. Because of this merit, Few layered 2DLMCs such as transition metal dichalcogenides (TMDs) (MoS 2 ,26, 27, 28 WS 2 ,29, 30, 31, 32, 33, 34, 35, 36 TiS 3 ,37 etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Monolayer MoSe 2 is a sandwich structure consisting of one Mo atom and two Se atoms, and the different layers are interacted by van der Waals force 20, 21. Like MoS 2 , the properties of MoSe 2 are also related with layer numbers; monolayer MoSe 2 exhibits a direct bandgap of 1.6 eV, whereas it changes into indirect bandgap of 1.1 eV for bulk or multilayer MoSe 2 22, 23. N‐type channel behavior with an average mobility of ≈50 cm 2 V −1 s −1 has been investigated for field‐effect transistors (FETs) based on monolayer MoSe 2 ,24 while for bulk MoSe 2 the carrier mobility is ≈100 cm 2 V −1 s −1 25.…”
mentioning
confidence: 99%